Apprenticeships - Backes-Gellner, Uschi [Verfasser]; Lehnert, Patrick [Verfasser] (My University, 2022)
“This article presents theoretical foundations and empirical evidence on the costs and benefits of dual apprenticeships, and shown that an investment in dual apprenticeships is beneficial for both individuals and firms in the short and long terms. Although research on the costs and benefits of dual apprenticeships is already steadily increasing, the field still offers a variety of valuable avenues for future research.“ (excerpt; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S 4.2 Kostenarten; 370; 330; Duales System; Berufsausbildung; Ausbildungskosten; Ausbildungsertrag; Bildungsinvestition; Kosten-Nutzen-Relation; Schweiz